Data article on elemental and metabolomic-based alkaloidal composition in black pepper oleoresin using a positive ESI-mode LC-QToF and ICP-mass spectroscopy - Olalere, Olusegun Abayomi; Nour, A. H.; R. M., Yunus; Alara, Oluwaseun Ruth (Elsevier Inc., 2018)
This paper contains data from the elemental and phytochemical profiling of black pepper oleoresin extracts using the LC–MS QToF and ICP-MS analysis. In recent years studies have shown the medicinal properties of extracts from these two cultivars of Piper nigrum. The medicinal properties are attributed to the presence of many secondary metabolites and mineral element in them. The phytochemical profiling was conducted using a Liquid Chromatography equipped with an electrospray time-of-flight mass spectrometer detectors. The mass spectrometer was equipped with an electrospray ionization sources operated in positive ion mode. The alkaloid compounds in the optimized black pepper extract were tentatively characterized in accordance with their ions׳ mass fragmentation.